Bartonella spp. and hematological changes in privately owned domestic cats from Rio de Janeiro, Brazil: Bartonella spp. in cats from Rio de Janeiro - Souza, Aline Moreira; Almosny, Nadia Regina Pereira; Favacho, Alexsandra Rodrigues Mendonça; Almeida, Daniele Nunes Pereira; Ferreira, Renata Fernandes; Ferreira, Eliane Oliveira; Moreira, Namir Santos; Lemos, Elba Regina Sampaio (The Journal of Infection in Developing Countries, 2017)
Introduction: Bartonella infection in cats can represent a risk to owners, particularly today when considering the increase in cat populations and their role in human bartonellosis epidemiology. In the present study, we aimed to detect Bartonella spp. in blood samples from 163 asymptomatic privately-owned cats from the metropolitan area of Rio de Janeiro State, Brazil by using a conventional PCR test and also to evaluate the association between Bartonella spp. and hematological changes in positive cats. Methodology: PCR assays were performed targeting the Bartonella spp heat shock protein (htrA) gene and complete blood counts were also performed in all samples. Positive PCR samples were confirmed by the presence of two genes, citrate synthase (gltA) and RNA polymerase beta-subunit-encoding (rpoB). Results: A total of 74.85% (122/163) of the tested cats were positive for Bartonella spp and partial sequencing confirmed to be B. henselae. All hematological findings from the 163 cats tested (PCR-positive and negative), presented normal limits. Conclusions: This study demonstrates that B. henselae is present in almost 75% asymptomatic privately-owned domestic cats in the metropolitan region of Rio de Janeiro State, Brazil. Our results also show that hematological findings in Bartonella spp. infected cats are uncommon. In this scenario, the use of PCR as a diagnostic tool in feline Bartonella infections should be considered. Finally, these results also demonstrate the potential risk of Bartonella spp. infection in the human population of the metropolitan area of Rio de Janeiro State, Brazil.